Be ready to fight new 5G vulnerabilities. Issue 10 (October 2018) - Sens, Ronald
Abstract : In the evolving landscape of mobile networks, we are beginning to see new vulnerabilities open up through 3G and 4G networks, and it is more than likely that 5G will follow this same fate. Protecting only this Gi Interface is no longer enough for any service providers' security. We are beginning to see new vulnerabilities open up through 3G and 4G networks, and it is more than likely that 5G will suffer the same fate. In addition to mitigating and stopping terabit-scale attacks coming from the Internet, it is imperative for enterprises to improve their security by using full-spectrum defences that protect the whole infrastructure. With the assistance of 5G service providers, businesses can then rest easy knowing they have multiple lines of defence, explains Ronald Sens at A10 Networks.